A paleomagnetic investigation of the Lower Ordovician St. George Group, Port-au-Port Peninsula, Newfoundland: implications for the Iapetus Ocean and evidence for Late Paleozoic remagnetization (Dataset) ... - Beaubouef, Rick; Casey, John F.; Hall, Stuart A.; Evans, Ian (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: A paleomagnetic investigation of the Lower Ordovician St. George Group, Port-au-Port Peninsula, Newfoundland: implications for the Iapetus Ocean and evidence for Late Paleozoic remagnetization ...